Essential role for both CD80 and CD86 costimulation, but not CD40 interactions, in allergen-induced Th2 cytokine production from asthmatic bronchial tissue: role for alphabeta, but not gammadelta, T cells - Jaffar, Z H; Stanciu, L; Pandit, A; Lordan, J; Holgate, S T; Roberts, K (The Journal of immunology (1950), 1999)
CD80 and CD86 interact with CD28 and deliver costimulatory signals required for T cell activation. We demonstrate that ex vivo allergen stimulation of bronchial biopsy tissue from mild atopic asthmatic, but not atopic nonasthmatic, subjects induced production of IL-5, IL-4, and IL-13. Explants from both study groups did not produce IFN-gamma, but secreted the chemokine RANTES without any overt stimulation. In addition to allergen, stimulation of asthmatic explants with mAbs to CD3 and TCR-alphabeta but not TCR-gammadelta induced IL-5 secretion. Allergen-induced IL-5 and IL-13 production by the asthmatic tissue was inhibited by anti-CD80 and, to a lesser extent, by anti-CD86 mAbs. In contrast, the production of these cytokines by PBMCs was not affected by mAbs to CD80, was inhibited by anti-CD86, and was strongly attenuated in the presence of both Abs. FACS analysis revealed that stimulated asthmatic bronchial tissue was comprised of CD4+ T cells that expressed surface CD28 (75. 3%) but little CTLA-4 (4.0%). Neutralizing mAbs to CD40 ligand had no effect on the cytokine levels produced by asthmatic tissue or PBMCs. Collectively, these findings suggest that allergen-specific alphabeta T cells are resident in asthmatic bronchial tissue and demonstrate that costimulation by both CD80 and CD86 is essential for allergen-induced cytokine production. In contrast, CD86 appears to be the principal costimulatory molecule required in PBMC responses. Attenuation of type 2 alphabeta T cell responses in the bronchial mucosa by blocking these costimulatory molecules may be of therapeutic potential in asthma.